Prosthodontic management of subtotal maxillectomy with minimally invasive interim obturator: a case report - Sreenivasulu, Duggineni; Reddy, N Simhachalam; Devarapalli, Sai Tejaswi (International Journal of Dental Materials, 2023)
The interim obturator serves as a pathway between the immediate or surgical obturator and the final prosthesis, offering functional and aesthetic benefits until the delivery of the definitive prosthesis. Furthermore, it acts as a guide during the fabrication of the definitive prosthesis, influencing aspects such as prosthesis extension, teeth arrangement, and the positioning of retentive aids. These aids may encompass orthodontic wiring, surgical suturing, and other non-invasive techniques. This case report details a conservative and less invasive method for retaining an interim obturator in maxillectomy patients, providing an alternative approach in prosthodontic care.